Strategi Pembelajaran Inklusi - Siti Asiatun; Heny Kusmawati; Syaiful Ma'arif; Komarudin Komarudin; Moh Rizal Muttaqin; Mujib Zuhdi (Departement of Mathematics Education, 2023)
Education is an instrument in shaping children's character so that they become a more qualified and independent generation. By nature, a child is born unique with different characters from one another. The difference can be in terms of physical and non-physical. And all of them must be able to be addressed by the education system and the method of attorney by positioning them according to their respective natures. Acts of discrimination both verbal and non-verbal in education must be eliminated and abolished because apart from violating government regulations it also violates the innate nature of a child. At SD Negeri Kedalingan 02 for example, where several children with special needs are given education and teaching according to their nature and needs. They are embraced so that self-confidence grows and they are nurtured using the among method and then directed to develop their potential without discrimination. And indeed educators and teachers have to work twice because they have to prepare two different devices at one time. In terms of their evaluation of the educators and teachers of SD Negeri Kedalingan 02 they are quite good although there are still some problems that must be addressed proportionately. On the other hand, parents in this case must be pro-active and mutually reinforcing for the good of their children in the future without reducing or denying the child's nature